The meaning of critical thinking from the perspective of international students - Malec-Rawiński, Małgorzata (Adult Education Discourses, 2020)
The general aim of this paper is to identify the meaning of critical thinking from the perspective of a sample of international students’ experiences and explain how that knowledge can be used to improve teaching. The main research question is: how do international student’s understand critical thinking? The author presents the data from a focus group discussion consisting of nine 1st year students in the Master of Education Program, at the Department of Education of Stockholm University (SU). The hermeneutical approach was used in both epistemological and methodological aspects as the framework for the analysis of the focus group discussion. One of the conclusions is that critical thinking is re/constructed and a part of lifelong and life-wide learning.